Bioselectivity of silk protein-based materials and their bio-inspired applications - Bargel, Hendrik; Trossmann, Vanessa T.; Sommer, Christoph; Scheibel, Thomas (Beilstein Journal of Nanotechnology, 2022)
Adhesion to material surfaces is crucial for almost all organisms regarding subsequent biological responses. Mammalian cell attachment to a surrounding biological matrix is essential for maintaining their survival and function concerning tissue formation. Conversely, the adhesion and presence of microbes interferes with important multicellular processes of tissue development. Therefore, tailoring bioselective, biologically active, and multifunctional materials for biomedical applications is a modern focus of biomaterial research. Engineering biomaterials that stimulate and interact with cell receptors to support binding and subsequent physiological responses of multicellular systems attracted much interest in the last years. Further to this, the increasing threat of multidrug resistance of pathogens against antibiotics to human health urgently requires new material concepts for preventing microbial infestation and biofilm formation. Thus, materials exhibiting microbial repellence or antimicrobial behaviour to reduce inflammation, while selectively enhancing regeneration in host tissues are of utmost interest. In this context, protein-based materials are interesting candidates due to their natural origin, biological activity, and structural properties. Silk materials, in particular those made of spider silk proteins and their recombinant counterparts, are characterized by extraordinary properties including excellent biocompatibility, slow biodegradation, low immunogenicity, and non-toxicity, making them ideally suited for tissue engineering and biomedical applications. Furthermore, recombinant production technologies allow for application-specific modification to develop adjustable, bioactive materials. The present review focusses on biological processes and surface interactions involved in the bioselective adhesion of mammalian cells and repellence of microbes on protein-based material surfaces. In addition, it highlights the importance of materials made of recombinant spider silk proteins, focussing on the progress regarding bioselectivity.
Keywords: antifouling; bacteriostatic; biofouling; bioselective cell adhesion; spider silk protein

(untitled) - Fazleabas, A. T.; Kim, J. J. (Science, 2003)

(untitled) - Keckes, J.; Burgert, I.; Frühmann, K.; Müller, M.; Kölln, K.; Hamilton, M.; Burghammer, M.; Roth, S. V.; Stanzl-Tschegg, S.; Fratzl, P. (Nat. Mater., 2003)

(untitled) - Melzer, B.; Steinbrecher, T.; Seidel, R.; Kraft, O.; Schwaiger, R.; Speck, T. (J. R. Soc., Interface, 2010)

(untitled) - Hofman, A. H.; van Hees, I. A.; Yang, J.; Kamperman, M. (Adv. Mater. (Weinheim, Ger.), 2018)

(untitled) - Gorb, S. N. (Philos. Trans. R. Soc., A, 2008)

(untitled) - Grunwald, I.; Rischka, K.; Kast, S. M.; Scheibel, T.; Bargel, H. (Philos. Trans. R. Soc., A, 2009)

Biological Adhesion - Smith, A. M. (Springer, 2016)

(untitled) - Rozario, T.; DeSimone, D. W. (Dev. Biol. (Amsterdam, Neth.), 2010)

(untitled) - Petruzzelli, L.; Takami, M.; Humes, H. D. (Am. J. Med., 1999)

(untitled) - Harjunpää, H.; Llort Asens, M.; Guenther, C.; Fagerholm, S. C. (Front. Immunol., 2019)

(untitled) - Sperandio, M. (FEBS J., 2006)

(untitled) - Samanta, D.; Almo, S. C. (Cell. Mol. Life Sci., 2015)

(untitled) - Aplin, A.; Howe, A.; Alahari, S.; Juliano, R. (Pharmacol. Rev., 1998)

(untitled) - Patel, S. D.; Chen, C. P.; Bahna, F.; Honig, B.; Shapiro, L. (Curr. Opin. Struct. Biol., 2003)

(untitled) - Yap, A. S.; Brieher, W. M.; Gumbiner, B. M. (Annu. Rev. Cell Dev. Biol., 1997)

(untitled) - Wai Wong, C.; Dye, D. E.; Coombe, D. R. (Int. J. Cell Biol., 2012)

(untitled) - Cayrol, R.; Wosik, K.; Berard, J. L.; Dodelet-Devillers, A.; Ifergan, I.; Kebir, H.; Haqqani, A. S.; Kreymborg, K.; Krug, S.; Moumdjian, R.; Bouthillier, A.; Becher, B.; et al. (Nat. Immunol., 2008)

(untitled) - Kappelmayer, J.; Nagy, B. (BioMed Res. Int., 2017)

(untitled) - Zhao, J.; Santino, F.; Giacomini, D.; Gentilucci, L. (Biomedicines, 2020)

(untitled) - Hynes, R. O. (Science, 2009)

(untitled) - Berrier, A. L.; Yamada, K. M. (J. Cell. Physiol., 2007)

(untitled) - Legate, K. R.; Wickström, S. A.; Fässler, R. (Genes Dev., 2009)

Biomaterials Science - Han, W. M.; Jang, Y. C.; García, A. J. (The Extracellular Matrix and Cell–Biomaterial Interactions, 2020)

(untitled) - Pankov, R.; Yamada, K. M. (J. Cell Sci., 2002)

(untitled) - De Marco, R.; Greco, A.; Calonghi, N.; Dattoli, S. D.; Baiula, M.; Spampinato, S.; Picchetti, P.; De Cola, L.; Anselmi, M.; Cipriani, F.; Gentilucci, L. (Pept. Sci., 2018)

(untitled) - Zhang, J.; Jiang, X.; Wen, X.; Xu, Q.; Zeng, H.; Zhao, Y.; Liu, M.; Wang, Z.; Hu, X.; Wang, Y. (JPhys Mater., 2019)

(untitled) - Mano, J. F. (Adv. Eng. Mater., 2008)

(untitled) - Gagner, J. E.; Kim, W.; Chaikof, E. L. (Acta Biomater., 2014)

Cutting-Edge Enabling Technologies for Regenerative Medicine - Choi, S. M.; Chaudhry, P.; Zo, S. M.; Han, S. S. (Advances in Protein-Based Materials: From Origin to Novel Biomaterials, 2018)

(untitled) - Annabi, N.; Mithieux, S. M.; Camci-Unal, G.; Dokmeci, M. R.; Weiss, A. S.; Khademhosseini, A. (Biochem. Eng. J., 2013)

(untitled) - Shin, H.; Jo, S.; Mikos, A. G. (Biomaterials, 2003)

(untitled) - Spiller, S.; Clauder, F.; Bellmann-Sickert, K.; Beck-Sickinger, A. G. (Biol. Chem., 2021)

(untitled) - Hosoyama, K.; Lazurko, C.; Muñoz, M.; McTiernan, C. D.; Alarcon, E. I. (Front. Bioeng. Biotechnol., 2019)

(untitled) - Huettner, N.; Dargaville, T. R.; Forget, A. (Trends Biotechnol., 2018)

(untitled) - Yamada, K. M. (J. Biol. Chem., 1991)

(untitled) - Pountos, I.; Panteli, M.; Lampropoulos, A.; Jones, E.; Calori, G. M.; Giannoudis, P. V. (BMC Med., 2016)

(untitled) - Ruoslahti, E.; Pierschbacher, M. D. (Cell, 1986)

(untitled) - Pierschbacher, M. D.; Hayman, E. G.; Ruoslahti, E. (J. Cell. Biochem., 1985)

(untitled) - Hersel, U.; Dahmen, C.; Kessler, H. (Biomaterials, 2003)

(untitled) - Pierschbacher, M. D.; Ruoslahti, E. (Nature, 1984)

(untitled) - Ruoslahti, E. (Annu. Rev. Cell Dev. Biol., 1996)

(untitled) - Bellis, S. L. (Biomaterials, 2011)

Integrin-Ligand Interaction - Pfaff, M. (Recognition Sites of RGD-Dependent Integrins, 1997)

(untitled) - Mertgen, A.-S.; Trossmann, V. T.; Guex, A. G.; Maniura-Weber, K.; Scheibel, T.; Rottmar, M. (ACS Appl. Mater. Interfaces, 2020)

(untitled) - Rechenmacher, F.; Neubauer, S.; Mas-Moruno, C.; Dorfner, P. M.; Polleux, J.; Guasch, J.; Conings, B.; Boyen, H.-G.; Bochen, A.; Sobahi, T. R.; Burgkart, R.; Spatz, J. P.; et al. (Chem. – Eur. J., 2013)

(untitled) - Grant, D. S.; Tashiro, K.-I.; Segui-Real, B.; Yamada, Y.; Martin, G. R.; Kleinman, H. K. (Cell, 1989)

(untitled) - Graf, J.; Iwamoto, Y.; Sasaki, M.; Martin, G. R.; Kleinman, H. K.; Robey, F. A.; Yamada, Y. (Cell, 1987)

(untitled) - Graf, J.; Ogle, R. C.; Robey, F. A.; Sasaki, M.; Martin, G. R.; Yamada, Y.; Kleinman, H. K. (Biochemistry, 1987)

(untitled) - Sullivan, T.; O’Callaghan, I. (Biomimetics, 2020)

(untitled) - Sonnleitner, D.; Sommer, C.; Scheibel, T.; Lang, G. (Mater. Sci. Eng., C, 2021)

(untitled) - Ivanova, E. P.; Hasan, J.; Webb, H. K.; Truong, V. K.; Watson, G. S.; Watson, J. A.; Baulin, V. A.; Pogodin, S.; Wang, J. Y.; Tobin, M. J.; Löbbe, C.; Crawford, R. J. (Small, 2012)

(untitled) - May, R. M.; Magin, C. M.; Mann, E. E.; Drinker, M. C.; Fraser, J. C.; Siedlecki, C. A.; Brennan, A. B.; Reddy, S. T. (Clin. Transl. Med., 2015)

(untitled) - Barthlott, W.; Mail, M.; Bhushan, B.; Koch, K. (Nano-Micro Lett., 2017)

(untitled) - Watson, G. S.; Green, D. W.; Cribb, B. W.; Brown, C. L.; Meritt, C. R.; Tobin, M. J.; Vongsvivut, J.; Sun, M.; Liang, A.-P.; Watson, J. A. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Barthlott, W.; Neinhuis, C. (Planta, 1997)

(untitled) - Barthlott, W.; Schimmel, T.; Wiersch, S.; Koch, K.; Brede, M.; Barczewski, M.; Walheim, S.; Weis, A.; Kaltenmaier, A.; Leder, A.; Bohn, H. F. (Adv. Mater. (Weinheim, Ger.), 2010)

(untitled) - Tripathy, A.; Sen, P.; Su, B.; Briscoe, W. H. (Adv. Colloid Interface Sci., 2017)

(untitled) - Liu, Q.; Brookbank, L.; Ho, A.; Coffey, J.; Brennan, A. B.; Jones, C. J. (PLoS One, 2020)

(untitled) - Koc, Y.; de Mello, A. J.; McHale, G.; Newton, M. I.; Roach, P.; Shirtcliffe, N. J. (Lab Chip, 2008)

(untitled) - Pernites, R. B.; Santos, C. M.; Maldonado, M.; Ponnapati, R. R.; Rodrigues, D. F.; Advincula, R. C. (Chem. Mater., 2012)

(untitled) - Stallard, C. P.; McDonnell, K. A.; Onayemi, O. D.; O’Gara, J. P.; Dowling, D. P. (Biointerphases, 2012)

(untitled) - Zhu, H.; Guo, Z.; Liu, W. (Chem. Commun., 2014)

(untitled) - Privett, B. J.; Youn, J.; Hong, S. A.; Lee, J.; Han, J.; Shin, J. H.; Schoenfisch, M. H. (Langmuir, 2011)

(untitled) - Crick, C. R.; Ismail, S.; Pratten, J.; Parkin, I. P. (Thin Solid Films, 2011)

(untitled) - Hizal, F.; Rungraeng, N.; Lee, J.; Jun, S.; Busscher, H. J.; van der Mei, H. C.; Choi, C.-H. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Cai, S.; Wu, C.; Yang, W.; Liang, W.; Yu, H.; Liu, L. (Nanotechnol. Rev., 2020)

(untitled) - Jeon, S. I.; Lee, J. H.; Andrade, J. D.; De Gennes, P. G. (J. Colloid Interface Sci., 1991)

(untitled) - Ista, L. K.; Mendez, S.; Lopez, G. P. (Biofouling, 2010)

(untitled) - Bosker, W. T. E.; Patzsch, K.; Stuart, M. A. C.; Norde, W. (Soft Matter, 2007)

(untitled) - Haldar, J.; An, D.; Álvarez de Cienfuegos, L.; Chen, J.; Klibanov, A. M. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Wong, S. Y.; Li, Q.; Veselinovic, J.; Kim, B.-S.; Klibanov, A. M.; Hammond, P. T. (Biomaterials, 2010)

(untitled) - Buzzacchera, I.; Vorobii, M.; Kostina, N. Y.; de los Santos Pereira, A.; Riedel, T.; Bruns, M.; Ogieglo, W.; Möller, M.; Wilson, C. J.; Rodriguez-Emmenegger, C. (Biomacromolecules, 2017)

(untitled) - Kovacs, B.; Patko, D.; Klein, A.; Kakasi, B.; Saftics, A.; Kurunczi, S.; Vonderviszt, F.; Horvath, R. (Sens. Actuators, B, 2018)

(untitled) - Liu, X.; Peng, L.; Meng, J.; Zhu, Z.; Han, B.; Wang, S. (Nanoscale, 2018)

(untitled) - Wang, L.-S.; Gopalakrishnan, S.; Lee, Y.-W.; Zhu, J.; Nonnenmann, S. S.; Rotello, V. M. (Mater. Horiz., 2018)

(untitled) - Bullitt, E.; Makowski, L. (Nature, 1995)

(untitled) - Garrett, T. R.; Bhakoo, M.; Zhang, Z. (Prog. Nat. Sci., 2008)

(untitled) - Asadi, A.; Razavi, S.; Talebi, M.; Gholami, M. (Infection (Munich, Ger.), 2019)

(untitled) - Piatek, R.; Zalewska-Piatek, B.; Dzierzbicka, K.; Makowiec, S.; Pilipczuk, J.; Szemiako, K.; Cyranka-Czaja, A.; Wojciechowski, M. (BMC Microbiol., 2013)

(untitled) - Pinkner, J. S.; Remaut, H.; Buelens, F.; Miller, E.; Åberg, V.; Pemberton, N.; Hedenström, M.; Larsson, A.; Seed, P.; Waksman, G.; Hultgren, S. J.; Almqvist, F. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Eidam, O.; Dworkowski, F. S. N.; Glockshuber, R.; Grütter, M. G.; Capitani, G. (FEBS Lett., 2008)

(untitled) - Soto, G. E.; Hultgren, S. J. (J. Bacteriol., 1999)

(untitled) - Krachler, A. M.; Ham, H.; Orth, K. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Krachler, A. M.; Mende, K.; Murray, C.; Orth, K. (Virulence, 2012)

(untitled) - Etayash, H.; Hancock, R. E. W. (Pharmaceutics, 2021)

(untitled) - Zasloff, M. (Nature, 2002)

(untitled) - Dürr, U. H. N.; Sudheendra, U. S.; Ramamoorthy, A. (Biochim. Biophys. Acta, Biomembr., 2006)

(untitled) - Lai, Y.; Gallo, R. L. (Trends Immunol., 2009)

(untitled) - Hancock, R. E. W.; Sahl, H.-G. (Nat. Biotechnol., 2006)

(untitled) - Lau, Y. E.; Rozek, A.; Scott, M. G.; Goosney, D. L.; Davidson, D. J.; Hancock, R. E. W. (Infect. Immun., 2005)

(untitled) - Duplantier, A. J.; van Hoek, M. L. (Front. Immunol., 2013)

(untitled) - Wimley, W. C.; Hristova, K. (J. Membr. Biol., 2011)

(untitled) - Wang, G.; Li, X.; Wang, Z. (Nucleic Acids Res., 2016)

(untitled) - Overhage, J.; Campisano, A.; Bains, M.; Torfs, E. C. W.; Rehm, B. H. A.; Hancock, R. E. W. (Infect. Immun., 2008)

(untitled) - de la Fuente-Núñez, C.; Korolik, V.; Bains, M.; Nguyen, U.; Breidenstein, E. B. M.; Horsman, S.; Lewenza, S.; Burrows, L.; Hancock, R. E. W. (Antimicrob. Agents Chemother., 2012)

(untitled) - Lee, J.-K.; Park, Y. (Int. J. Mol. Sci., 2020)

(untitled) - Godballe, T.; Nilsson, L. L.; Petersen, P. D.; Jenssen, H. (Chem. Biol. Drug Des., 2011)

(untitled) - Bicker, K. L.; Cobb, S. L. (Chem. Commun., 2020)

(untitled) - Beckloff, N.; Laube, D.; Castro, T.; Furgang, D.; Park, S.; Perlin, D.; Clements, D.; Tang, H.; Scott, R. W.; Tew, G. N.; Diamond, G. (Antimicrob. Agents Chemother., 2007)

(untitled) - Tagliabue, A.; Rappuoli, R. (Front. Immunol., 2018)

(untitled) - Bloom, D. E.; Cadarette, D. (Front. Immunol., 2019)

(untitled) - He, T.; Shi, Z. L.; Fang, N.; Neoh, K. G.; Kang, E. T.; Chan, V. (Biomaterials, 2009)

(untitled) - He, T.; Zhang, Y.; Lai, A. C. K.; Chan, V. (Biomed. Mater., 2015)

(untitled) - Altman, G. H.; Diaz, F.; Jakuba, C.; Calabro, T.; Horan, R. L.; Chen, J.; Lu, H.; Richmond, J.; Kaplan, D. L. (Biomaterials, 2003)

(untitled) - Salehi, S.; Koeck, K.; Scheibel, T. (Molecules, 2020)

(untitled) - Aigner, T. B.; DeSimone, E.; Scheibel, T. (Adv. Mater. (Weinheim, Ger.), 2018)

(untitled) - Kiseleva, A. P.; Krivoshapkin, P. V.; Krivoshapkina, E. F. (Front. Chem. (Lausanne, Switz.), 2020)

Ullmann's Encyclopedia of Industrial Chemistry - Scheibel, T.; Zahn, H.; Krasowski, A. (Silk, 2016)

(untitled) - Herold, H. M.; Scheibel, T. (Z. Naturforsch., C: J. Biosci., 2017)

(untitled) - Sehnal, F.; Sutherland, T. (Prion, 2008)

(untitled) - Garb, J. E.; Ayoub, N. A.; Hayashi, C. Y. (BMC Evol. Biol., 2010)

(untitled) - Sutherland, T. D.; Young, J. H.; Weisman, S.; Hayashi, C. Y.; Merritt, D. J. (Annu. Rev. Entomol., 2010)

(untitled) - Andersson, M.; Johansson, J.; Rising, A. (Int. J. Mol. Sci., 2016)

(untitled) - Saric, M.; Scheibel, T. (Curr. Opin. Biotechnol., 2019)

(untitled) - Inoue, S.; Tanaka, K.; Arisaka, F.; Kimura, S.; Ohtomo, K.; Mizuno, S. (J. Biol. Chem., 2000)

(untitled) - Sehadova, H.; Zavodska, R.; Rouhova, L.; Zurovec, M.; Sauman, I. (Int. J. Mol. Sci., 2021)

(untitled) - Kucerova, L.; Zurovec, M.; Kludkiewicz, B.; Hradilova, M.; Strnad, H.; Sehnal, F. (Sci. Rep., 2019)

(untitled) - Eisoldt, L.; Smith, A.; Scheibel, T. (Mater. Today, 2011)

(untitled) - Eisoldt, L.; Thamm, C.; Scheibel, T. (Biopolymers, 2012)

(untitled) - Bittencourt, D.; Oliveira, P. F.; Prosdocimi, F.; Rech, E. L. (Genet. Mol. Res., 2012)

(untitled) - Thamm, C.; Scheibel, T. (Biomacromolecules, 2017)

(untitled) - Collin, M. A.; Clarke, T. H., III; Ayoub, N. A.; Hayashi, C. Y. (Int. J. Biol. Macromol., 2018)

(untitled) - Altman, G. H.; Horan, R. L.; Lu, H. H.; Moreau, J.; Martin, I.; Richmond, J. C.; Kaplan, D. L. (Biomaterials, 2002)

(untitled) - Ribeiro, M.; de Moraes, M. A.; Beppu, M. M.; Garcia, M. P.; Fernandes, M. H.; Monteiro, F. J.; Ferraz, M. P. (Eur. Polym. J., 2015)

(untitled) - Kuhbier, J. W.; Allmeling, C.; Reimers, K.; Hillmer, A.; Kasper, C.; Menger, B.; Brandes, G.; Guggenheim, M.; Vogt, P. M. (PLoS One, 2010)

(untitled) - Wendt, H.; Hillmer, A.; Reimers, K.; Kuhbier, J. W.; Schäfer-Nolte, F.; Allmeling, C.; Kasper, C.; Vogt, P. M. (PLoS One, 2011)

(untitled) - Yang, M.; Shuai, Y.; Zhou, G.; Mandal, N.; Zhu, L.; Mao, C. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Pedregal-Cortés, R.; Toriz, G.; Delgado, E.; Pollack, G. H. (Biofouling, 2019)

(untitled) - Chigama, H.; Yokoi, T.; Furuya, M.; Yokota, K.; Kanetaka, H.; Kawashita, M. (J. Mater. Sci.: Mater. Med., 2020)

(untitled) - Amaley, A.; Gawali, A. A.; Akarte, S. R. (Indian J. Arachnol., 2014)

(untitled) - Wright, S.; Goodacre, S. L. (BMC Res. Notes, 2012)

(untitled) - Tahir, H. M.; Zaheer, A.; Rasheed, A.; Mukhtar, M. K.; Yaqoob, R.; Liaqat, I.; Ahsan, M. M. (Acta Zool. Bulg., 2018)

(untitled) - Tahir, M.; Sattar, A.; Qamar, S.; Mukhtar, M.; Liaqat, I.; Ali, M.; Zaheer, A.; Arshad, N.; Yaqoob, R.; Naseem, S. (J. Anim. Plant Sci., 2019)

(untitled) - Carl, N. K.; Alexander, E. D.; Taylor, A. S.; Jessica, A. R.; Jonathan, N. P. (J. Arachnol., 2015)

(untitled) - Makover, V.; Ronen, Z.; Lubin, Y.; Khalaila, I. (J. R. Soc., Interface, 2019)

(untitled) - Zhang, S.; Piorkowski, D.; Lin, W.-R.; Lee, Y.-R.; Liao, C.-P.; Wang, P.-H.; Tso, I.-M. (J. Exp. Biol., 2019)

(untitled) - Kaur, J.; Rajkhowa, R.; Afrin, T.; Tsuzuki, T.; Wang, X. (Biopolymers, 2014)

(untitled) - Fruergaard, S.; Lund, M. B.; Schramm, A.; Vosegaard, T.; Bilde, T. (iScience, 2021)

(untitled) - Whittall, D. R.; Baker, K. V.; Breitling, R.; Takano, E. (Trends Biotechnol., 2021)

(untitled) - Heidebrecht, A.; Scheibel, T. (Adv. Appl. Microbiol., 2013)

(untitled) - Hedhammar, M.; Rising, A.; Grip, S.; Martinez, A. S.; Nordling, K.; Casals, C.; Stark, M.; Johansson, J. (Biochemistry, 2008)

(untitled) - Stark, M.; Grip, S.; Rising, A.; Hedhammar, M.; Engström, W.; Hjälm, G.; Johansson, J. (Biomacromolecules, 2007)

(untitled) - Huemmerich, D.; Helsen, C. W.; Quedzuweit, S.; Oschmann, J.; Rudolph, R.; Scheibel, T. (Biochemistry, 2004)

(untitled) - Doblhofer, E.; Scheibel, T. (J. Pharm. Sci., 2015)

(untitled) - Kumari, S.; Lang, G.; DeSimone, E.; Spengler, C.; Trossmann, V. T.; Lücker, S.; Hudel, M.; Jacobs, K.; Krämer, N.; Scheibel, T. (Data Brief, 2020)

(untitled) - Kumari, S.; Lang, G.; DeSimone, E.; Spengler, C.; Trossmann, V. T.; Lücker, S.; Hudel, M.; Jacobs, K.; Krämer, N.; Scheibel, T. (Mater. Today, 2020)

(untitled) - Rabotyagova, O. S.; Cebe, P.; Kaplan, D. L. (Biomacromolecules, 2009)

(untitled) - Wohlrab, S.; Müller, S.; Schmidt, A.; Neubauer, S.; Kessler, H.; Leal-Egaña, A.; Scheibel, T. (Biomaterials, 2012)

(untitled) - Neubauer, V. J.; Scheibel, T. (ACS Biomater. Sci. Eng., 2020)

(untitled) - Esser, T. U.; Trossmann, V. T.; Lentz, S.; Engel, F. B.; Scheibel, T. (Mater. Today Bio, 2021)

(untitled) - Widhe, M.; Shalaly, N. D.; Hedhammar, M. (Biomaterials, 2016)

(untitled) - Widhe, M.; Johansson, U.; Hillerdahl, C.-O.; Hedhammar, M. (Biomaterials, 2013)

(untitled) - Nilebäck, L.; Hedin, J.; Widhe, M.; Floderus, L. S.; Krona, A.; Bysell, H.; Hedhammar, M. (Biomacromolecules, 2017)

(untitled) - Johansson, U.; Ria, M.; Åvall, K.; Dekki Shalaly, N.; Zaitsev, S. V.; Berggren, P.-O.; Hedhammar, M. (PLoS One, 2015)

(untitled) - Saric, M.; Eisoldt, L.; Döring, V.; Scheibel, T. (Adv. Mater. (Weinheim, Ger.), 2021)

(untitled) - Jansson, R.; Lau, C. H.; Ishida, T.; Ramström, M.; Sandgren, M.; Hedhammar, M. (Biotechnol. J., 2016)

(untitled) - Jansson, R.; Thatikonda, N.; Lindberg, D.; Rising, A.; Johansson, J.; Nygren, P.-Å.; Hedhammar, M. (Biomacromolecules, 2014)

(untitled) - Humenik, M.; Mohrand, M.; Scheibel, T. (Bioconjugate Chem., 2018)

(untitled) - Thatikonda, N.; Nilebäck, L.; Kempe, A.; Widhe, M.; Hedhammar, M. (ACS Biomater. Sci. Eng., 2018)

(untitled) - Thatikonda, N.; Delfani, P.; Jansson, R.; Petersson, L.; Lindberg, D.; Wingren, C.; Hedhammar, M. (Biotechnol. J., 2016)

(untitled) - Leal-Egaña, A.; Lang, G.; Mauerer, C.; Wickinghoff, J.; Weber, M.; Geimer, S.; Scheibel, T. (Adv. Eng. Mater., 2012)

(untitled) - Petzold, J.; Aigner, T. B.; Touska, F.; Zimmermann, K.; Scheibel, T.; Engel, F. B. (Adv. Funct. Mater., 2017)

(untitled) - Borkner, C. B.; Wohlrab, S.; Möller, E.; Lang, G.; Scheibel, T. (ACS Biomater. Sci. Eng., 2017)

(untitled) - Leal-Egaña, A.; Díaz-Cuenca, A.; Boccaccini, A. R. (Adv. Mater. (Weinheim, Ger.), 2013)

(untitled) - Blau, A. (Curr. Opin. Colloid Interface Sci., 2013)

(untitled) - De Rosa, M.; Carteni', M.; Petillo, O.; Calarco, A.; Margarucci, S.; Rosso, F.; De Rosa, A.; Farina, E.; Grippo, P.; Peluso, G. (J. Cell. Physiol., 2004)

(untitled) - Widhe, M.; Bysell, H.; Nystedt, S.; Schenning, I.; Malmsten, M.; Johansson, J.; Rising, A.; Hedhammar, M. (Biomaterials, 2010)

(untitled) - Kramer, J. P. M.; Aigner, T. B.; Petzold, J.; Roshanbinfar, K.; Scheibel, T.; Engel, F. B. (Sci. Rep., 2020)

(untitled) - Schacht, K.; Vogt, J.; Scheibel, T. (ACS Biomater. Sci. Eng., 2016)

(untitled) - Tasiopoulos, C. P.; Gustafsson, L.; van der Wijngaart, W.; Hedhammar, M. (ACS Biomater. Sci. Eng., 2021)

(untitled) - Schacht, K.; Scheibel, T. (Biomacromolecules, 2011)

(untitled) - DeSimone, E.; Schacht, K.; Pellert, A.; Scheibel, T. (Biofabrication, 2017)

(untitled) - Neubauer, V. J.; Trossmann, V. T.; Jacobi, S.; Döbl, A.; Scheibel, T. (Angew. Chem., Int. Ed., 2021)

(untitled) - Schacht, K.; Jüngst, T.; Schweinlin, M.; Ewald, A.; Groll, J.; Scheibel, T. (Angew. Chem., Int. Ed., 2015)

(untitled) - Steiner, D.; Winkler, S.; Heltmann-Meyer, S.; Trossmann, V. T.; Fey, T.; Scheibel, T.; Horch, R. E.; Arkudas, A. (Biofabrication, 2021)

(untitled) - Shalaly, N. D.; Ria, M.; Johansson, U.; Åvall, K.; Berggren, P.-O.; Hedhammar, M. (Biomaterials, 2016)

(untitled) - Szymkowiak, P.; Tsiareshyna, M.; Koczura, R. (Biologia (Cham, Switz.), 2020)

(untitled) - Alicea-Serrano, A. M.; Bender, K.; Jurestovsky, D. (J. Arachnol., 2020)

(untitled) - Harris, T. I.; Gaztambide, D. A.; Day, B. A.; Brock, C. L.; Ruben, A. L.; Jones, J. A.; Lewis, R. V. (Biomacromolecules, 2016)

(untitled) - Gomes, S. C.; Leonor, I. B.; Mano, J. F.; Reis, R. L.; Kaplan, D. L. (Biomaterials, 2011)

(untitled) - Liu, F. Y. C. (bioRxiv, 2021)

(untitled) - Nilebäck, L.; Chouhan, D.; Jansson, R.; Widhe, M.; Mandal, B. B.; Hedhammar, M. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Chouhan, D.; Thatikonda, N.; Nilebäck, L.; Widhe, M.; Hedhammar, M.; Mandal, B. B. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Huang, T.; Kumari, S.; Herold, H.; Bargel, H.; Aigner, T. B.; Heath, D. E.; O'Brien-Simpson, N. M.; O'Connor, A. J.; Scheibel, T. (Int. J. Nanomed., 2020)

(untitled) - Brennan, S. A.; Ní Fhoghlú, C.; Devitt, B. M.; O’Mahony, F. J.; Brabazon, D.; Walsh, A. (Bone Jt. J., 2015)

(untitled) - Li, Y.; Lin, Z.; Zhao, M.; Xu, T.; Wang, C.; Hua, L.; Wang, H.; Xia, H.; Zhu, B. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Seong, M.; Lee, D. G. (Curr. Microbiol., 2017)

(untitled) - Khalandi, B.; Asadi, N.; Milani, M.; Davaran, S.; Abadi, A. J. N.; Abasi, E.; Akbarzadeh, A. (Drug Res. (Stuttgart, Ger.), 2017)

(untitled) - Yu, D.; Kang, G.; Tian, W.; Lin, L.; Wang, W. (Appl. Surf. Sci., 2015)

(untitled) - Tang, B.; Li, J.; Hou, X.; Afrin, T.; Sun, L.; Wang, X. (Ind. Eng. Chem. Res., 2013)

(untitled) - Tang, B.; Sun, L.; Kaur, J.; Yu, Y.; Wang, X. (Dyes Pigm., 2014)

(untitled) - Nadiger, V. G.; Shukla, S. R. (J. Text. Inst., 2016)

(untitled) - Doakhan, S.; Montazer, M.; Rashidi, A.; Moniri, R.; Moghadam, M. B. (Carbohydr. Polym., 2013)

(untitled) - He, H.; Cai, R.; Wang, Y.; Tao, G.; Guo, P.; Zuo, H.; Chen, L.; Liu, X.; Zhao, P.; Xia, Q. (Int. J. Biol. Macromol., 2017)

(untitled) - Tao, G.; Cai, R.; Wang, Y.; Liu, L.; Zuo, H.; Zhao, P.; Umar, A.; Mao, C.; Xia, Q.; He, H. (Mater. Des., 2019)

(untitled) - Currie, H. A.; Deschaume, O.; Naik, R. R.; Perry, C. C.; Kaplan, D. L. (Adv. Funct. Mater., 2011)

(untitled) - Khalid, A.; Bai, D.; Abraham, A. N.; Jadhav, A.; Linklater, D.; Matusica, A.; Nguyen, D.; Murdoch, B. J.; Zakhartchouk, N.; Dekiwadia, C.; Reineck, P.; Simpson, D.; et al. (ACS Appl. Mater. Interfaces, 2020)

(untitled) - Kumari, S.; Bargel, H.; Scheibel, T. (Macromol. Rapid Commun., 2020)

(untitled) - Harvey, D.; Bardelang, P.; Goodacre, S. L.; Cockayne, A.; Thomas, N. R. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Seijsing, F.; Nilebäck, L.; Öhman, O.; Pasupuleti, R.; Ståhl, C.; Seijsing, J.; Hedhammar, M. (MicrobiologyOpen, 2020)

(untitled) - Zeplin, P. H.; Berninger, A.-K.; Maksimovikj, N. C.; van Gelder, P.; Scheibel, T.; Walles, H. (Handchir., Mikrochir., Plast. Chir., 2014)

(untitled) - Zeplin, P. H.; Maksimovikj, N. C.; Jordan, M. C.; Nickel, J.; Lang, G.; Leimer, A. H.; Römer, L.; Scheibel, T. (Adv. Funct. Mater., 2014)

(untitled) - Sommer, C.; Bargel, H.; Raßmann, N.; Scheibel, T. (MRS Commun., 2021)

(untitled) - Zhang, Y.; Zhou, Z.; Sun, L.; Liu, Z.; Xia, X.; Tao, T. H. (Adv. Mater. (Weinheim, Ger.), 2018)

(untitled) - Weiss, A. C. G.; Herold, H. M.; Lentz, S.; Faria, M.; Besford, Q. A.; Ang, C.-S.; Caruso, F.; Scheibel, T. (ACS Appl. Mater. Interfaces, 2020)

(untitled) - Mulinti, P.; Diekjürgen, D.; Kurtzeborn, K.; Balasubramanian, N.; Stafslien, S. J.; Grainger, D. W.; Brooks, A. E. (Bioengineering, 2022)

(untitled) - Zha, R. H.; Delparastan, P.; Fink, T. D.; Bauer, J.; Scheibel, T.; Messersmith, P. B. (Biomater. Sci., 2019)